Auscultate, palpate and tap: time to re‐evaluate. (23rd October 2015) - Hawkes, GA; Hawkes, CP; Kenosi, M; Demeulemeester, J; Livingstone, V; Ryan, CA; Dempsey, EM
Abstract: Aim: To determine the accuracy of current methods of heart rate (HR) assessment. Methods: All participants palpated a simulated pulsating umbilicus (UMB), listened to a tapping rate (TAP) and auscultated a simulated HR (AUSC). A simulated HR of 54, 88 and 128 beats per minute (bpm) was randomised for all methods. Results: Twenty‐nine healthcare staff participated in this study. Correct assessment of HR of 54 bpm as being within the 0‐59 range occurred in 17.2% UMB, 17.2% TAP and 31% AUSC and was obtained in <10 seconds by 48.3%, 65.5% and 62.1%, respectively. A rate of 88 bpm was correctly assessed as within the 60–100 range in 82.8% UMB, 79.3% TAP and 79.3% AUSC and was obtained in <10 seconds by 55.2%, 58.6% and 55.2%, respectively. A rate of 128 bpm was identified as >100 bpm by 96.6% UMB, 93.1% TAP, and 93.1% AUSC and was obtained in <10 seconds by 51.7%, 55.2% and 62.1%, respectively. Conclusion: Current methods in assessing rates below 60 bpm are inaccurate and may overestimate HR. We recommend that these methods alone should not be relied upon in neonatal resuscitation and objective assessment of heart rate should be readily available at all newborn resuscitations.